Striatin Is Required for Hearing and Affects Inner Hair Cells and Ribbon Synapses - Nadar-Ponniah, Prathamesh T.; Taiber, Shahar; Caspi, Michal; Koffler-Brill, Tal; Dror, Amiel A.; Siman-Tov, Ronen; Rubinstein, Moran; Padmanabhan, Krishnanand; Luxenburg, Chen; Lang, Richard A.; Avraham, Karen B.; Rosin-Arbesfeld, Rina (Frontiers in Cell and Developmental Biology, 2020)
Striatin, a subunit of the serine/threonine phosphatase PP2A, is a core member of the conserved striatin-interacting phosphatase and kinase (STRIPAK) complexes. The protein is expressed in the cell junctions between epithelial cells, which play a role in maintaining cell-cell adhesion. Since the cell junctions are crucial for the function of the mammalian inner ear, we examined the localization and function of striatin in the mouse cochlea. Our results show that in neonatal mice, striatin is specifically expressed in the cell-cell junctions of the inner hair cells, the receptor cells in the mammalian cochlea. Auditory brainstem response measurements of striatin-deficient mice indicated a progressive, high-frequency hearing loss, suggesting that striatin is essential for normal hearing. Moreover, scanning electron micrographs of the organ of Corti revealed a moderate degeneration of the outer hair cells in the middle and basal regions, concordant with the high-frequency hearing loss. Importantly, striatin-deficient mice show aberrant ribbon synapse maturation that may lead to the observed auditory impairment. Together, these results suggest a novel function for striatin in the mammalian auditory system.